Maskulinisasi Ikan Guppy (Poecilia Reticulata) Melalui Metode Perendaman Induk Menggunakan Air Kelapa Dengan Konsentrasi Berbeda - Tasya Alivia Novitasari; Sri Hidayati; Eric Armando (Departemen Akuakultur FPIK UNDIP, 2023)
This study was conducted to analyse the use of coconut water doses to achieve a higher percentage of males in guppy breeding and how it affects the survival of guppy fry. The search took place in Mertoyudan, Magelang district between November 2021 and January 2022. This research plan was a completely randomized design with 4 treatments and 4 replicates. Treatments in this study were immersed in gravid females at 0%; 50%; 55%; and 60% solution concentration of coconut water. The data were analysed using a One Way ANOVA followed by the Least Significant Difference test. Results from the data analysis showed that gravid females were immersed in a coconut water solution increased the percentage of male guppy fry with the addition of coconut water doses used. The highest percentage of male guppy fry was 87.7% achieved in the immersion treatment at a 60% coconut water with a 100% survival rate.Keywords : coconut water, guppy (Poecilia reticulata), guppies gravid female, males in guppy